15th Conference on Data Analysis Methods for Software Systems. November 28–30, 2024 - Bernatavičienė, Jolita (Vilnius University Proceedings, 2024)
DAMSS-2024 is the 15th International Conference on Data Analysis Methods for Software Systems. It is held in Druskininkai, Lithuania, at the same venue and time every year. The conference successfully achieves its primary goal of lively scientific communication among participants. The conference’s history dates back to 2009 when 16 papers were presented. It began as a workshop related to one international project and has evolved into a well-known conference. The initiator of the workshop was the Institute of Mathematics and Informatics which later became the Institute of Data Science and Digital Technologies at Vilnius University. The Lithuanian Academy of Sciences and the Lithuanian Computer Society are partners. The long-standing experience of such partnerships guarantees a high quality of organization and academic relevance.